Involvement of the Autophagy Protein Atg6 in Development and Virulence in the Gray Mold Fungus Botrytis cinerea - Liu, Na; Zhou, Shanyue; Li, Baohua; Ren, Weichao (Frontiers in Microbiology, 2021)
Gray mold caused by Botrytis cinerea is a devastating disease that leads to huge economic losses worldwide. Autophagy is an evolutionarily conserved process that maintains intracellular homeostasis through self-eating. In this study, we identified and characterized the biological function of the autophagy-related protein Atg6 in B. cinerea. Targeted deletion of the BcATG6 gene showed block of autophagy and several phenotypic defects in aspects of mycelial growth, conidiation, sclerotial formation and virulence. All of the phenotypic defects were restored by targeted gene complementation. Taken together, these results suggest that BcAtg6 plays important roles in the regulation of various cellular processes in B. cinerea.